Cell Viability and Immunogenic Function of T Cells Loaded with Nanoparticles for Spatial Guidance in Magnetic Fields - Pfister, Felix; Alexiou, Christoph; Janko, Christina (Humana Press Inc., 2023)
Immune cell therapies, such as adoptive T cell therapies, are an innovative and powerful treatment option for previously non-treatable diseases. Although immune cell therapies are thought to be very specific, there is still the danger of developing severe to life-threatening side effects due to the unspecific distribution of the cells throughout the body (on-target/off-tumor effects). A possible solution for the reduction of these side effects and the improvement of tumor infiltration is the specific targeting of the effector cells (e.g., T cells) to the desired destination (e.g., tumor region). This can be achieved by the magnetization of cells with superparamagnetic iron oxide nanoparticles (SPIONs) for spatial guidance via external magnetic fields. A prerequisite for the use of SPION-loaded T cells in adoptive T cell therapies is that cell viability and functionality after nanoparticle loading are preserved. Here, we demonstrate a protocol to analyze cell viability and functionality such as activation, proliferation, cytokine release, and differentiation at a single cell level using flow cytometry.
CRIS-Team Scopus Importer:2023-05-26
Keywords: Cell viability; Flow cytometry; Intracellular cytokine staining; T cells; T cell activation; T cell proliferation